RELATIONSHIP OF KNOWLEDGE AND ATTITUDE TO THE PREVENTION OF TYPE II DIABETES MELLITUS AMONG STUDENTS OF PUBLIC HEALTH UNDERGRADUATE DEGREE PROGRAM - Novalina Retno Nugraheni; Muhammad Atoillah Isfandiari (The Indonesian Journal of Public Health, 2022)
Introduction: Diabetes mellitus (DM) is a degenerative disease that causes the body's tissues or organs to deteriorate over time. One of the provinces in Indonesia with the highest prevalence of diabetes is the province of East Java. Knowledge related to DM type II should have been instilled since school. When someone has enough knowledge, it will form good attitudes and actions. This study aims to study the relationship between attitudes and knowledge of public health students with actions related to the prevention of DM type II. Methods: This type of research is analytic descriptive research with cross-sectional research design. The study population was all S1 Public Health Sciences students, amounting to 870 students. The sampling technique is total sampling / saturated sample. So the size of the study sample is 870 students. This study uses prevalence ratio (PR) analysis to determine the strong relationship between variables and the magnitude of risk. Result: The homework between knowledge and action variables shows a value of 1,114 (95% CI = 0.888 – 1.399) and the prevalence ratio value between attitude and action variables shows a value of 0.597 (95% CI = 0.490 - 0.726). Conclusion: Suggestions from this researcher are making public service advertisements about student compliance and awareness about healthy lifestyle habits, especially restrictions on foods high in sugar, limiting eating fast food, doing proper and regular exercise, and getting enough sleep.